2018
DOI: 10.1016/j.pedneo.2017.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Influence of platelet count, platelet mass index, and platelet function on the spontaneous closure of ductus arteriosus in the prematurity

Abstract: This is the first study in the English literature providing evidence of the influence of platelet dysfunction on the spontaneous closure of ductus arteriosus in prematurity. Longer collagen-ADP duration is identified as a risk factor of ductal closure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 27 publications
1
42
2
2
Order By: Relevance
“…Also, in another meta‐analysis, platelet count appeared lower in premature infants who did not respond to the first medical treatment . In the following limited number of studies, the role of platelet indices in ductal patency was investigated, but no clear relationship was found . There is also scant data regarding the value of plateletcrit (PCT) in PDA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, in another meta‐analysis, platelet count appeared lower in premature infants who did not respond to the first medical treatment . In the following limited number of studies, the role of platelet indices in ductal patency was investigated, but no clear relationship was found . There is also scant data regarding the value of plateletcrit (PCT) in PDA.…”
Section: Introductionmentioning
confidence: 99%
“…6 In the following limited number of studies, the role of platelet indices in ductal patency was investigated, but no clear relationship was found. [7][8][9][10][11] There is also scant data regarding the value of plateletcrit (PCT) in PDA.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggested that platelet count and functions play an important role in the closure of ductus arteriosus, while some others did not find any relationship between the ductal closure and platelet count and functions. [6][7][8] High platelet count and mean platelet volume (MPV) have been shown to support ductal closure by promoting thrombosis inside the lumen of arterial duct. Large platelets are known to be more active.…”
Section: The Fate Of Patent Ductus Arteriosus Is Notmentioning
confidence: 99%
“…They identified longer collagen-ADP duration as a risk factor for ductal closure, although there were no differences in platelet count, mean platelet volume (MPV), and platelet mass index between the open and closed ductus groups. 1 Clinical studies investigating the impact of platelet count on ductal patency in human preterm infants have reported conflicting results, and it is speculated that platelet dysfunction, rather than low platelet count, is the primary contributory factor for the failure of ductal closure in preterm infants. 1,2 We had recently reported that median serum platelet-derived growth factor levels were significantly lower among babies who subsequently required medical treatment for ductal patency.…”
mentioning
confidence: 99%
“…1 Clinical studies investigating the impact of platelet count on ductal patency in human preterm infants have reported conflicting results, and it is speculated that platelet dysfunction, rather than low platelet count, is the primary contributory factor for the failure of ductal closure in preterm infants. 1,2 We had recently reported that median serum platelet-derived growth factor levels were significantly lower among babies who subsequently required medical treatment for ductal patency. Our results suggested that platelet-derived growth factor may play a role in ductal closure independent of platelet count and might be used as an adjunct surrogate for prediction of the future need for treatment of hemodynamically significant patent ductus arteriosus in preterm infants.…”
mentioning
confidence: 99%